Analisis isi Pesan Dakwah Studi Kasus Pada Majalah tanwirul afkar edisi 564 tahun 2023 “Musuh Baru Para Buruh” - Nadia; Hasyim; Assilah, Qonita (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2025)
This research aims to analyze the content of the da'wah message in Tanwirul Afkar magazine, edition 564 in 2023 with the theme "The New Enemy of Workers" in the article on religious fatwas in the era of artificial intelligence. The two main problem formulations studied in this research are: (1) how the da'wah message in Tanwirul Afkar magazine is presented regarding religious fatwas in the era of artificial intelligence, and (2) how Tanwirul Afkar magazine views religious fatwas in the era of artificial intelligence.This research uses qualitative content analysis methods and da'wah communication theory to examine the da'wah messages conveyed in the article. Data was obtained through documentation techniques by examining the text in the magazine in depth. The results of the analysis show that the presentation of the da'wah message in the article highlights the challenges and opportunities faced by Muslims in the era of artificial intelligence. This article emphasizes the importance of using technology wisely and ethically within the framework of Islamic teachings. In addition, the da'wah message in the article includes messages of morals, sharia, and creed, all of which are put together to provide practical and ethical guidance for readers in dealing with technological developments. Tanwirul Afkar magazine's perspective on religious fatwas in the era of artificial intelligence is shown through a balanced and realistic approach. This article acknowledges the threat that artificial intelligence poses to workers' jobs, but also emphasizes its potential benefits if used wisely.